Should the maximum duration of fixed-term contracts increase in recessions? Evidence from a law reform - Pedro S. Martins (Global Labor Organization (GLO), 2017)
Fixed-term contracts (FTCs) may be an important tool to promote employment, particularly in recessions or when permanent contracts are costly. Therefore, it may be useful to vary some of the legal parameters of FTCs over the business cycle, namely increasing their flexibility during downturns. We evaluate this idea by examining the effects of a 2011 law that increased the maximum duration of FTCs in Portugal, in the midst of a recession. Our analysis is based on regression-discontinuity (and difference-in-differences) methods and linked panel data. We find a considerable take up of this measure, as conversions to permanent contracts drop by 20%. Worker churning is reduced significantly, as mobility of eligible fixed-term workers to other firms drops by 10%. Employment also increases significantly for younger workers.
Keywords: J23; J41; J63; 330; Employment law; worker mobility; segmentation; counterfactual evaluation